1975
DOI: 10.1002/ccd.1810010108
|View full text |Cite
|
Sign up to set email alerts
|

Inotropic Action of Tolbutamide on Human Myocardium

Abstract: The inotropic action of tolbutamide previously demonstrated in vitro was evaluated in 15 nondiabetic subjects during diagnostic cardiac catheterization. Following bolus injection of 250 mg of tolbutamide intravenously, a rise of serum insulin and a slight fall of serum potassium were observed. Inotropic response was determined from significant fall in PEP/LVET ratio, significant fall of left ventricular end-diastolic pressure, shift to an augmented function curve in work-pressure relationships, and prominent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
1997
1997

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Moreover, several studies (Lasseter et al 1972 ;Hildner et al 1975) have reported that a concentration of tolbutamide of 0.1-1.0mM produces a positive inotropic effect. The authers had previously observed prostacyclin synthesis by cultured endothelial cells, using thin-layer radiochromatography (Kawaguchi et al 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies (Lasseter et al 1972 ;Hildner et al 1975) have reported that a concentration of tolbutamide of 0.1-1.0mM produces a positive inotropic effect. The authers had previously observed prostacyclin synthesis by cultured endothelial cells, using thin-layer radiochromatography (Kawaguchi et al 1982).…”
Section: Discussionmentioning
confidence: 99%